Peranan Guru dalam Manajemen Peserta Didik - Rahayu Anggraeni; Anne Effane (KARIMAH TAUHID, 2022)
In the world of education, the role and duties of the teacher are very important factors. The teacher is the most important part in the teaching and learning process both in formal and informal learning paths. Therefore, with all the improvements in the quality of education in the country, it is impossible to separate the various problems related to the existence of teachers. Learning is essentially a causal process. The teacher as a teacher is the main cause of student learning, although not all student learning is the result of teaching the teacher. Therefore, the teacher as a central figure must be able to determine appropriate learning strategies to encourage students to carry out active, productive and effective learning activities. In teaching the teacher must pay attention to the readiness, maturity and behavior of their students, therefore the teacher has an important position and strategy to create a good and fun learning atmosphere that guides students to achieve goals as well as possible. The teacher must be able to position himself as a multiplier, communicator, facilitator, transformer, organizer, promoter, motivator and evaluator to create a dynamic and innovative learning process for students. Learning is a conscious effort made by educators or teachers to convey information by organizing and creating a learning environment system using various ways so that students can carry out learning activities optimally. Even though the term "learning" is used, this does not mean that the teacher has to let go as an employer. In the context of learning, this does not mean expanding the role of students on the one hand and reducing the role of the teacher on the other. Teachers must be able to take an important role in learning. So, the role and role of the teacher in the context of student learning must be balanced because the two cannot stand alone but need one another.